(untitled) (International Journal of Ayurveda and Pharma Research, 2024)
Ayurveda has described various preventions as well as cure for every disorder. This all helps in maintaining health of an individual. Ayurveda has mentioned Aahara, Nidra, Brahmacharya are the three main pillars of body. Nidra is essential in every person’s life. Here Nidra is explained as one of the important part of life which provides Sukha, Dukha etc. Ayurveda has mentioned that lack of Nidra causes ‘Nidranasha’. According to Ayurveda, Nidranasha i.e., insomnia classified under the Vatananatmaja Vikara. There are various treatments and Kalpas etc. available for the management of Nidranasha. In this case report of Nidranasha patient was treated with Ayurvedic management with Shodhana and Shamana Chikitsa. Shirodhara helps to relieve the stress, along with reduces Chinta, etc Manasa Bhava.